Re-Understanding Gender Relations About Authority Rights as Marriage Guardians : Arabic Grammatical Perspective - M. Syamsul Rizal; Athoillah Islamy (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2020)
This study aims to find an Arabic grammatical analysis of several verses, both in the Koran and the Hadith that describe the authority of the rights as guardians of marriage. This type of research is a qualitative research in the form of literature review. The main data source, namely the foundation of the nas (al-Qur'an verse and Hadith) which describes the existence of a marriage guardian. Secondary data sources, namely various other relevant studies. The research analysis approach used is the linguistic approach (Arabic grammar). Meanwhile, the theory used as a knife of analysis is gender identity theory in Arabic. This study concludes that the use of verbs, both the commandment and prohibition of marriage in several verses of the Koran and Hadith cannot necessarily be claimed to be specifically aimed at men as long as there are no indicators that indicate their specificity.